Living with the past: the creation of the stolen generation positionality. (September 2019) - Gilbert, Stephanie
That you could look down to your arm and hands and see brown skin, but it connote nothing but disgust or confusion, is one consequence of the assimilationist policies implemented on Aborigines throughout Australia in the 1900s. Some removed children had little exposure or experience of Aboriginal culture, family and no reinforcement to live "as an Aborigine". Understanding the disconnect experienced by these removed children, between being visually perceived as Aboriginal and living an identity they have been forced to create is important. This article describes how this disconnect is understood as a dysphoria holding both body-focused aspects and cultural aspects. It is proposed here that these dysphoric constructions have resulted in a unique way within this population and influences how the individuals involved have come to understand their lived identity and, indeed, how they might continue to be understood as a legitimate part of the span of indigeneities.